Towards legal harmonization of the crime of human trafficking in Venezuela: A perspective from the philosophy of human rights - Acosta Araujo, Alejandro Alberto; Díaz Saavedra, Eduardo Enrique (Frónesis, 2023)
This study examines the classification of the crime of human trafficking within the Venezuelan legal framework from a human rights philosophy, acknowledging the devastating consequences for the victims and its alarming proliferation in Latin America and the world. From a scientific-legal perspective, it has been possible to identify some notions of the criminal type and its consideration within the Venezuelan legal framework, contrasting these findings with the standards established by international conventions and treaties ratified by the Bolivarian Republic of Venezuela. Through a meticulous descriptive bibliographic research methodology, documentary observation and juridical hermeneutic analysis on secondary sources were employed to unravel the legal implications and the existing gaps in the legislation. The results highlight an alarming disparity: while the Law for a Woman’s Right to a Life Free of Violence recognizes this crime, the Venezuelan Penal Code omits its classification, creating legal voids that hinder the fight against this scourge. This conclusion underlines the urgent need for legal reforms that harmonize national legislation with international commitments, to strengthen protection mechanisms for victims and eradicate human trafficking, especially that affecting women and children.